2015
DOI: 10.1177/2055207615580741
|View full text |Cite
|
Sign up to set email alerts
|

Managing stress through the Stress Free app: Practices of self-care in digitally mediated spaces

Abstract: In this paper we are concerned with the question of how we feel when living in concert with multiple technologies. More specifically, we are focused on the influx of digital apps designed to manage psychological wellbeing. We draw on empirical work exploring one such app, Stress Free, and focus on the experiences of stress and technological tools designed to lessen stress. Our concern is with the way that technologies become part of the experience of stress as opposed to solely understanding the app as a tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Other barriers mentioned by participants also converge with those of previous research pointing out the stress-inducing potential of these apps [ 9 ]. Specifically, some participants saw prepopulated questions about their feelings as stress inducing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Other barriers mentioned by participants also converge with those of previous research pointing out the stress-inducing potential of these apps [ 9 ]. Specifically, some participants saw prepopulated questions about their feelings as stress inducing.…”
Section: Discussionsupporting
confidence: 78%
“…Adolescents’ familiarity with mobile devices suggests that technology-based approaches would benefit them [ 8 ]; however, it is crucial to understand how best to tailor digital interventions to make them the most appealing. Tucker and Goodings [ 9 ] identified three themes that characterize most current MHapps, as follows: stress-inducing or stress-reducing apps, apps for configuring the body in space, and digital self-care apps. However, apps targeting adolescents likely need to expand into other areas such as positive focus, customizable features, human-human interaction, and easy access [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic spaces can also be digitally-mediated,17 and this was evident in the stories. Online discussion forums were singled out over other digital media as key spaces where people could find reassurance, comfort, feeling less alone and solutions for how they should address or resolve their health problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of social research on people’s use of apps and wearable devices has begun to demonstrate that these technologies can help people achieve better knowledge of their bodies and health, self-care and fitness goals. This research has also shown that health apps and wearable devices can also demand invisible labour from users, while some people consider them to be overly intrusive 13–17. For some intended users, health apps or wearable devices are viewed as irrelevant, as they do not offer the information or support people need, or are viewed as being poorly designed for the specificities of people’s lives 13 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…There was also a high preference for adolescents with high anxiety/depression scores to include an anxiety/depression symptom assessment questionnaire, but research contradicts this finding. Specifically, they report that the predetermined options for characterizing situations were "too restrictive" or "quite imprecise" for some adolescents (Kenny et al, 2016), as was the case with the predetermined options on automatic thoughts, which contributed to increased anxiety (Tucker & Goodings, 2015). However, other research has praised mental health apps for their ability to increase users' emotional awareness (Morris et al, 2010;Kauer et al, 2012), which is a key parameter of cognitive-behavioural therapy (Clark, 2013), and by extension a prerequisite for effective user engagement (Ribanszki et al, 2021).…”
Section: Operation/contentmentioning
confidence: 99%